Positive electrode plate for lead-acid battery, negative electrode plate for lead-acid battery, and lead-acid battery

By optimizing the specific conductance and structural ratios of electrode plates in lead-acid batteries, sulfation is suppressed, improving cycle life performance through surface-focused discharge reactions.

JP2025012336APending Publication Date: 2025-01-24GS YUASA CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023115099
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-13
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Lead-acid batteries experience sulfation, where lead sulfate recrystallizes and becomes coarse, leading to deteriorated cycle life performance due to electrolyte stratification and uneven current distribution within the electrode plates.

Method used

The positive and negative electrode plates are designed with specific conductance values of 1.8 S/mm or less for the positive electrode and 120 S/mm or less for the negative electrode, along with optimized ratios of areas surrounded by grid bars and controlled BET specific surface areas to concentrate discharge reactions near the surface, inhibiting internal sulfation.

Benefits of technology

This design suppresses sulfation, enhancing cycle life performance by forming a thin layer of lead sulfate near the electrode surface and preventing its formation inside the plates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025012336000001_ABST
    Figure 2025012336000001_ABST
Patent Text Reader

Abstract

SOLUTION: To provide a positive electrode plate for a lead-acid battery which includes a positive current collector and a positive electrode material held on the positive current collector, and in which the specific conductance of the positive electrode material is 1.8 S / mm or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a positive electrode plate for a lead-acid battery, a negative electrode plate for a lead-acid battery, and a lead-acid battery. [Background technology]

[0002] Lead-acid batteries are used in a variety of applications, including automotive and industrial use. Lead-acid batteries include negative and positive plates, a separator (or mat), and an electrolyte. Each plate includes a current collector and an electrode material.

[0003] In lead-acid batteries, attempts have been made to add ceramic flakes to electrode materials in order to improve the electrical conductivity of the electrode materials.

[0004] Patent Document 1 describes a method for producing a thin film having a thickness of 0.1 μm to 5 μm, an average radius of the flakes of 50 μm or more, and a resistivity of 9×10 -2 We have proposed a lead-acid battery in which oxide-based conductive ceramic flakes, characterized by a resistance of less than Ω·cm, are mixed as an additive.

[0005] Also, in lead-acid batteries, attempts have been made to change the shape of the grid in order to suppress capacity reduction and short circuits caused by the falling off of electrode material.

[0006] Patent Document 2 proposes an electrode plate for a lead-acid battery, which uses an expanded lattice manufactured by machining a lead alloy sheet to form a continuous expanded lattice that is partially cut and expanded, filling the continuous expanded lattice with paste, and then cutting it to a specified size, characterized in that the expanded lattice is cut so that no nodes of the lattice rungs remain on both sides of the expanded lattice of the electrode plate, and the distance between a lattice side and the nearest node opposing the lattice side is approximately 1 / 4 of the diagonal distance parallel to the traveling direction of the continuous lattice of a polygon that is the smallest unit mesh shape formed by the nodes and the lattice rungs, with a plurality of nodes as vertices.

[0007] Patent document 3 proposes an expanded mesh sheet of a predetermined length obtained by simultaneously subjecting a band-shaped metal sheet to uneven processing in the thickness direction and cutting in the longitudinal direction, expanding the metal sheet in the width direction, and cutting the expanded mesh sheet along a cutting line along the width direction, in which the expanded mesh sheet has a lattice pattern in which approximately diamond-shaped lattice elements surrounded by four linear lattice frames are connected by nodes arranged in a staggered pattern, and at both ends in the longitudinal direction, a plurality of approximately triangular deformed lattice elements surrounded by three of the lattice frames are connected in a row in the width direction, and each of the lattice frames located at the end of each of these deformed lattice elements is connected in a substantially straight line along the width direction. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Japanese Patent Application Publication No. 06-187820 [Patent Document 2] Japanese Patent Application Publication No. 10-223232 [Patent Document 3] Japanese Patent Application Publication No. 7-320743 Summary of the Invention [Problem to be solved by the invention]

[0009] In lead-acid batteries, stratification occurs when high-concentration electrolyte settles at the bottom of the plate during charging, causing a large amount of discharge at the bottom of the plate, resulting in a phenomenon called sulfation, in which lead sulfate recrystallizes and coarsens. As a result, cycle life performance decreases, so there is a need to suppress sulfation in order to improve cycle life performance. [Means for solving the problem]

[0010] One aspect of the present invention is a positive electrode plate for a lead-acid battery, A positive electrode current collector and a positive electrode material held by the positive electrode current collector, The positive electrode material has a specific conductance of 1.8 S / mm or less.

[0011] Another aspect of the present invention is a negative electrode plate for a lead-acid battery, A negative electrode current collector and a negative electrode material held by the negative electrode current collector, The negative electrode material has a specific conductance of 120 S / mm or less.

[0012] Another aspect of the present invention relates to a lead-acid battery including at least one of the positive electrode plate for a lead-acid battery of the present invention and the negative electrode plate for a lead-acid battery of the present invention. Effect of the Invention

[0013] According to the present invention, a positive electrode plate for a lead-acid battery having a high sulfation suppressing effect can be obtained. [Brief description of the drawings]

[0014] [Figure 1] 1 is a partially cutaway exploded perspective view showing the appearance and internal structure of a lead-acid battery according to one aspect of the present invention; [Figure 2A] FIG. 2 is a top view illustrating a schematic diagram of a current collector used in the lead-acid battery according to one aspect of the present invention. [Figure 2B] 2B is a diagram showing a schematic view of a region surrounded by lattice bars of a lattice portion in the top view shown in FIG. 2A. FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The lead-acid battery positive electrode plate according to this embodiment includes a positive electrode current collector and a positive electrode material held by the positive electrode current collector. The area of ​​the lattice part of the positive electrode current collector may be referred to as "SP0", and the total area of ​​the region surrounded by the lattice bars of the lattice part of the positive electrode current collector may be referred to as "SP1". The ratio of the area SP1 to the area SP0 may be referred to as the "ratio SP1 / SP0".

[0016] The negative electrode plate for a lead-acid battery according to this embodiment includes a negative electrode current collector and a negative electrode material held by the negative electrode current collector. The area of ​​the lattice-shaped portion of the negative electrode current collector may be referred to as "SN0", and the total area of ​​the region surrounded by the lattice bars of the negative electrode current collector may be referred to as "SN1". The ratio of the area SN1 to the area SN0 may be referred to as the "ratio SN1 / SN0".

[0017] The area surrounded by the lattice bars of the positive and negative current collectors means the area surrounded by the lattice bars constituting the lattice part of each current collector in a plane perpendicular to the thickness direction of each current collector as shown in FIG. 2. When calculating SP1 and SN1, the upper frame part and the lower frame part of each current collector are also considered as part of the lattice bars, and the area surrounded by the lattice bars of each current collector is defined. From one point of view, the area surrounded by the lattice bars is an area surrounded by a closed ring structure formed by the lattice bars. Examples of closed ring structures include circular rings, polygonal rings (triangular rings, square rings, other polygonal rings), or ring structures equivalent thereto. Therefore, for example, an area that is not partially surrounded by the lattice bars constituting each current collector, such as the end of the current collector, is not included in the area surrounded by the lattice bars of each current collector. The area of ​​the area surrounded by the lattice bars of the lattice part of the positive current collector defined by the above method corresponds to "SP1", and the area of ​​the area surrounded by the lattice bars of the lattice part of the negative current collector corresponds to "SN1".

[0018] The inventors considered that the coarsening of lead sulfate is likely to occur inside the electrode material (the region that is deep in the thickness direction from the interface between the electrode material surface and the electrolyte to the electrode plate), and that the cause is the difference in the ease of current flow between the surface area of ​​the electrode material and the inside of the electrode material. Since current flows more easily near the surface of the electrode material than inside the electrode material, lead sulfate is less likely to remain. On the other hand, since current does not flow easily inside the electrode material, lead sulfate is more likely to remain. As a result, it is thought that sulfation, in which the remaining lead sulfate coarsens, is more likely to progress. Therefore, the inventors attempted to confine the charge / discharge reaction to the surface area of ​​the electrode material in order to suppress the coarsening of lead sulfate inside the electrode material.

[0019] In view of the above, a positive electrode plate for a lead-acid battery according to one aspect of the present invention includes a positive electrode current collector and a positive electrode material held by the positive electrode current collector, and the specific conductance of the positive electrode material is 1.8 S / mm or less.

[0020] By setting the specific conductance of the positive electrode material to 1.8 S / mm or less, the sulfation suppression effect can be enhanced, and the cycle life performance can be improved. The mechanism by which the sulfation suppression effect is obtained is not clear, but is speculated as follows. When the specific conductance of the electrode material is large as in the past, the discharge reaction easily reaches the inside of the electrode material, and lead sulfate is likely to remain inside the electrode material. On the other hand, when the specific conductance of the electrode material is made smaller than in the past, it becomes difficult for current to flow to the electrode material, and the discharge reaction is difficult to reach the inside of the electrode material. As a result, the discharge reaction that generates lead sulfate is biased toward the surface of the electrode material, and a thin layer of lead sulfate is likely to form near the surface of the electrode material. In this case, since lead sulfate is difficult to form inside the electrode material, the coarsening of the lead sulfate remaining inside the electrode material is suppressed, and lead sulfate is also suppressed from remaining inside the electrode material, so that a positive electrode plate for a lead-acid battery with a high sulfation suppression effect can be obtained.

[0021] A negative electrode plate for a lead-acid battery according to another aspect of the present invention includes a negative electrode current collector and a negative electrode material held on the negative electrode current collector, the specific conductance of the negative electrode material being 120 S / mm or less.

[0022] By setting the specific conductance of the negative electrode material to 120 S / mm or less, the sulfation suppression effect can be enhanced, leading to improved cycle life performance. The mechanism by which the sulfation suppression effect is obtained is thought to be the same as that of the positive plate for lead-acid batteries, in that by making the specific conductance of the electrode material smaller than that of conventional materials, the discharge reaction is less likely to reach the inside of the electrode material, and the discharge reaction that produces lead sulfate is biased toward the surface of the electrode material, making it easier for a thin layer of lead sulfate to form near the surface of the electrode material. As a result, lead sulfate is prevented from remaining inside the electrode material, resulting in a negative plate for lead-acid batteries with a high sulfation suppression effect.

[0023] The specific conductance of the positive electrode material is, for example, 1.4 S / mm or less, and may be 1.0 S / mm or less.

[0024] By setting the specific conductance of the positive electrode material to 0.6 S / mm or more, the risk of a decrease in high-rate discharge performance can be reduced. By setting the specific conductance of the positive electrode material to 0.6 S / mm or more, the risk of the discharge reaction being extremely biased toward the surface of the electrode material, the entire surface of the electrode material being covered with lead sulfate, and an increase in resistance between the surface of the electrode material and the electrolyte can be reduced.

[0025] The specific conductance of the negative electrode material is, for example, 100 S / mm or less, and may be 80 S / mm or less.

[0026] By making the specific conductance of the negative electrode material 40 S / mm or more, the risk of a decrease in high-rate discharge performance can be reduced. By making the specific conductance of the negative electrode material 40 S / mm or more, the risk of the discharge reaction being extremely biased toward the surface of the electrode material, the entire surface of the electrode material being covered with lead sulfate, and an increase in resistance between the surface of the electrode material and the electrolyte can be reduced.

[0027] The ratio SP1 / SP0 is preferably 0.68 or more. By making the ratio SP1 / SP0 0.68 or more, the sulfation suppression effect can be further enhanced, and the cycle life performance can be improved. When the ratio SP1 / SP0 is smaller than a predetermined value, the area not surrounded by the lattice bars of the positive electrode current collector at the end of the current collector where the current does not easily flow is large, so that the positive electrode material filled in this area is difficult to charge and discharge. As a result, the charge and discharge reaction of the positive electrode material is concentrated in the center of the plate, so that even if the specific conductance of the positive electrode material is reduced, it is difficult to form a thin lead sulfate layer near the surface of the positive electrode material, and the sulfation suppression effect cannot be sufficiently obtained. On the other hand, when the ratio SP1 / SP0 is larger than a predetermined value, the area not surrounded by the lattice bars of the positive electrode current collector at the end of the current collector where the current does not easily flow is small, so that the charge and discharge reaction of the positive electrode material is easily uniformed over the entire plate. As a result, the charge and discharge reaction is difficult to concentrate in a specific area in the direction horizontal to the plate, and it is easy to form a thin lead sulfate layer near the surface of the positive electrode material. This effect can be obtained by combining a positive electrode current collector with a large ratio SP1 / SP0 with a positive electrode material with a small specific conductance, making it possible to obtain a positive electrode plate for a lead-acid battery that has a high sulfation suppression effect.

[0028] The ratio SN1 / SN0 is preferably 0.65 or more. By making the ratio SN1 / SN0 0.65 or more, the sulfation suppression effect can be further enhanced, and the cycle life performance can be improved. The mechanism by which the sulfation suppression effect is obtained is presumed to be the same as that of the positive plate for a lead-acid battery, in that when the ratio SN1 / SN0 is greater than a predetermined value, the charge / discharge reaction of the negative electrode material is uniformed throughout the plate, making it difficult for the charge / discharge reaction to concentrate, and making it easier to form a thin layer of lead sulfate near the surface of the negative electrode material. This effect can be obtained by combining a negative electrode current collector with a large ratio SN1 / SN0 with a negative electrode material with a small specific conductance, and a negative plate for a lead-acid battery with a high sulfation suppression effect can be obtained.

[0029] The ratio SP1 / SP0 may be, for example, 0.70 or greater.

[0030] By setting the ratio SP1 / SP0 to 0.90 or less, the node pitch of the positive electrode current collector (the distance between the nodes of the lattice bars in the width direction of the current collector) can be increased, reducing the risk of the lattice bars breaking when expanded during the current collector manufacturing process.

[0031] The ratio SN1 / SN0 may be, for example, 0.67 or greater.

[0032] By setting the ratio SN1 / SN0 to 0.90 or less, the node pitch of the negative electrode current collector (the distance between the nodes of the lattice bars in the width direction of the current collector) can be increased, reducing the risk of the lattice bars breaking when expanded during the current collector manufacturing process.

[0033] The grid-like portion of the positive electrode current collector and the grid-like portion of the negative electrode current collector are preferably expanded grids. In an expanded grid, since there is no frame portion in the width direction of the current collector and the charge / discharge reaction of the electrode material tends to concentrate in the center of the electrode plate, it is easy to obtain an effect by increasing the ratio SP1 / SP0 or the ratio SN1 / SN0. In addition, in the manufacturing process of the expanded grid, the ratio SP1 / SP0 or the ratio SN1 / SN0 can be easily controlled by changing the cutting position of the current collector or the distance between the nodes, so that the present invention is suitable for application.

[0034] The BET specific surface area of ​​the positive electrode material is 5.8m 2 / g or more. BET specific surface area is 5.8m 2 / g or more, the sulfation suppression effect can be further enhanced, and the cycle life performance can be improved. When the BET specific surface area is smaller than a predetermined value, the surface of the positive electrode material where the discharge reaction can occur is limited, so even if the specific conductance of the positive electrode material is reduced, a thick layer of lead sulfate is likely to be formed near the surface of the positive electrode material. On the other hand, when the BET specific surface area is larger than a predetermined value, the surface area of ​​the positive electrode material where the discharge reaction can occur is large. Therefore, when the specific conductance of the positive electrode material is small and the BET specific surface area is large, the charge / discharge reaction can be performed on a wide surface of the positive electrode material, so that a thinner layer of lead sulfate is likely to be formed. This effect can be obtained when the specific conductance of the positive electrode material is smaller than a predetermined value and the BET specific surface area of ​​the positive electrode material is larger than a predetermined value, and a positive plate for a lead-acid battery with a high sulfation suppression effect can be obtained.

[0035] The BET specific surface area of ​​the negative electrode material is 0.75 m 2 / g or more. BET specific surface area is 0.75 m 2 / g or more, the sulfation suppression effect can be further enhanced, and the cycle life performance can be improved. The mechanism by which the sulfation suppression effect is obtained is considered to be that, as with the positive plate for a lead-acid battery, when the BET specific surface area is larger than a predetermined value, the charge / discharge reaction can be carried out on a wide surface of the negative electrode material, making it easier to form a thinner layer of lead sulfate. This effect is obtained when the specific conductance of the negative electrode material is smaller than a predetermined value and the BET specific surface area of ​​the negative electrode material is larger than a predetermined value, and a negative plate for a lead-acid battery with a high sulfation suppression effect can be obtained.

[0036] The BET specific surface area of ​​the positive electrode material is, for example, 6.4 m 2 / g or more, and 7.0m 2 / g or more, and 7.6m 2 / g or more.

[0037] The BET specific surface area of ​​the positive electrode material is 11.0 m 2By setting the pore size at 0.1 to 0.1 / g or less, the pore size of the positive electrode material becomes very small, and the risk of pore clogging caused by lead sulfate generated during discharge and a decrease in discharge capacity can be reduced. In addition, by making the pore clogging less likely to occur, charge and discharge reactions can be more easily carried out on a wider surface of the positive electrode material. As a result, a thin layer of lead sulfate can be easily formed on the surface of the positive electrode material, and a positive plate for a lead-acid battery with a high sulfation suppression effect can be obtained.

[0038] The BET specific surface area of ​​the negative electrode material is, for example, 0.80 m 2 / g or more, and 0.85m 2 / g or more, and 0.90m 2 / g or more.

[0039] The BET specific surface area of ​​the negative electrode material is 1.1 m 2 By setting the pore size at 0.1 to 0.1 / g or less, the pore size of the negative electrode material becomes very small, and the risk of pore clogging caused by lead sulfate generated during discharge and a decrease in discharge capacity can be reduced. In addition, by making the pore clogging less likely to occur, charge / discharge reactions can be more easily carried out on a wider surface of the negative electrode material. As a result, a thin layer of lead sulfate can be easily formed on the surface of the negative electrode material, and a negative electrode plate for a lead-acid battery with a high sulfation suppression effect can be obtained.

[0040] The lead acid battery of the present invention includes at least one of the positive electrode plate for a lead acid battery of the present invention and the negative electrode plate for a lead acid battery of the present invention. By including these electrodes, sulfation of the lead acid battery can be suppressed and cycle life performance can be improved. The lead acid battery of the present invention may include the positive electrode plate for a lead acid battery of the present invention, may include the negative electrode plate for a lead acid battery of the present invention, or may include both of them.

[0041] (fully charged) In this specification, the fully charged state of a flooded lead-acid battery is defined by JIS D 5301: 2019. More specifically, the fully charged state is defined as a state in which a lead-acid battery is charged in a water tank at 25°C ± 2°C with a current (A) that is 0.2 times the value (unit: Ah) described as the rated capacity, until the terminal voltage (V) during charging or the electrolyte density converted to a temperature of 20°C shows a constant value with three significant digits three consecutive times.

[0042] In this specification, a fully charged lead-acid battery is a lead-acid battery that has already been chemically formed and is fully charged. The lead-acid battery may be fully charged immediately after chemical formation, or may be fully charged after a certain period of time has passed since chemical formation (for example, a lead-acid battery that is in use (preferably in the early stages of use) after chemical formation may be fully charged). An early stage battery is a battery that has not been in use for very long and has hardly deteriorated at all.

[0043] (electrode material) The negative electrode material and the positive electrode material are usually held by a current collector. The electrode material is the portion of the electrode plate excluding the current collector. A member such as a mat or pasting paper may be attached to the electrode plate. Such a member (also called an attachment member) is included in the electrode plate because it is used integrally with the electrode plate. When the electrode plate includes an attachment member (such as a mat or pasting paper), the electrode material is the portion of the electrode plate excluding the current collector and the attachment member.

[0044] Hereinafter, the lead-acid battery according to the embodiment of the present invention will be described in detail with respect to each of its main components, but the present invention is not limited to the following embodiment.

[0045] [Lead acid battery] (Positive plate) The positive electrode plate includes a positive electrode material and a positive electrode current collector. In one example of a method for manufacturing a positive electrode plate, a positive electrode paste is first applied or filled onto a positive electrode current collector, and then aged and dried to produce an unformed positive electrode plate. The unformed positive electrode plate is then formed into a positive electrode plate by chemically forming the positive electrode plate. The positive electrode paste that serves as the positive electrode material is prepared, for example, by kneading lead powder, an additive as required, water, and sulfuric acid (or an aqueous sulfuric acid solution). The unformed positive electrode plate may be aged at a temperature higher than room temperature and at a high humidity.

[0046] The formation can be carried out by immersing an electrode plate group including unformed positive plates in an electrolyte solution containing sulfuric acid in a battery container of a lead-acid battery and charging the electrode plate group in this state. However, the formation may also be carried out before assembling the lead-acid battery or the electrode plate group.

[0047] (Positive electrode current collector) The positive electrode current collector may be formed by casting lead (Pb) or a lead alloy, or may be formed by processing a lead sheet or a lead alloy sheet. Examples of the processing method include expanding and punching. It is preferable to use a lattice-shaped current collector as the positive electrode current collector because it is easy to support the positive electrode material.

[0048] Examples of lead alloys used in the positive electrode current collector include Pb-Sb based alloys, Pb-Ca based alloys, Pb-Ca-Sn based alloys, etc. The lead alloy may further contain at least one kind selected from the group consisting of Ba, Ag, Al, Bi, As, Se, Cu, etc. as an additive element.

[0049] (Positive electrode material) The positive electrode material contained in the positive electrode plate contains a positive electrode active material (lead dioxide or lead sulfate) that develops capacity through an oxidation-reduction reaction. The positive electrode material may contain other additives as necessary.

[0050] (Negative plate) The negative plate includes a negative electrode material and a negative electrode current collector. In one example of a method for manufacturing a negative electrode plate, a negative electrode paste is first applied or filled onto a negative electrode current collector, and then aged and dried to produce an unformed negative electrode plate. The unformed negative electrode plate is then formed into a negative electrode plate by chemically forming the negative electrode plate. The negative electrode paste that serves as the negative electrode material is prepared, for example, by kneading lead powder, water, and sulfuric acid (or an aqueous sulfuric acid solution), and optionally a polymer compound and other additives. The unformed negative electrode plate may be aged at a temperature higher than room temperature and at a high humidity.

[0051] The formation can be carried out, for example, by immersing an electrode plate group including unformed negative plates in an electrolyte containing sulfuric acid in a lead-acid battery container and charging the electrode plate group. However, the formation may be carried out before assembling the lead-acid battery or the electrode plate group. The formation produces spongy lead.

[0052] (Negative electrode current collector) The negative electrode current collector may be formed by casting lead (Pb) or a lead alloy, or may be formed by processing a lead sheet or a lead alloy sheet. Examples of the processing method include expanding and punching. It is preferable to use a lattice-shaped current collector as the negative electrode current collector because it is easy to support the negative electrode material.

[0053] The lead alloy used for the negative electrode current collector may be any of Pb-Sb alloy, Pb-Ca alloy, and Pb-Ca-Sn alloy. These lead or lead alloys may further contain at least one selected from the group consisting of Ba, Ag, Al, Bi, As, Se, Cu, etc. as an additive element. The negative electrode current collector may have a surface layer. The surface layer and the inner layer of the negative electrode current collector may have different compositions. The surface layer may be formed on a part of the negative electrode current collector. The surface layer may be formed on the ear of the negative electrode current collector. The surface layer of the ear may contain Sn or an Sn alloy.

[0054] (Negative electrode material) The negative electrode material contains a negative electrode active material (specifically, lead or lead sulfate) that develops capacity through an oxidation-reduction reaction. The negative electrode material may contain at least one selected from the group consisting of an organic shrinkage inhibitor, a carbonaceous material, and other additives. Examples of additives include, but are not limited to, barium sulfate and fibers (such as resin fibers). Note that the negative electrode active material in a charged state is sponge-like lead, but an unformed negative plate is usually made using lead powder.

[0055] (Organic shrink-proofing agent) The organic shrinkage inhibitor is an organic compound that inhibits the shrinkage of lead, which is the negative electrode active material, when the lead-acid battery is repeatedly charged and discharged. As the organic shrinkage inhibitor, for example, at least one selected from the group consisting of lignin compounds and synthetic organic shrinkage inhibitors may be used.

[0056] Examples of the lignin compound include lignin and lignin derivatives. Examples of the lignin derivatives include lignin sulfonic acid or salts thereof (alkali metal salts (sodium salts, etc.)).

[0057] The content of the organic shrinkage preventer in the negative electrode material is preferably, for example, 0.005% by mass or more.

[0058] (carbonaceous material) Carbon black, graphite, hard carbon, soft carbon, etc. can be used as the carbonaceous material contained in the negative electrode material. Examples of carbon black include acetylene black, furnace black, lamp black, etc. Furnace black also includes Ketjen Black (trade name). Graphite may be any carbonaceous material containing a graphite-type crystal structure, and may be either artificial graphite or natural graphite. The negative electrode material may contain one type of carbonaceous material, or may contain two or more types.

[0059] The content of the carbonaceous material in the negative electrode material is, for example, 0.05 mass% or more, and may be 0.10 mass% or more.The content of the carbonaceous material is, for example, 5 mass% or less, and may be 3 mass% or less.

[0060] The content of the carbonaceous material in the negative electrode material may be 0.05% by mass or more and 5% by mass or less, 0.05% by mass or more and 3% by mass or less (or 1.2% by mass or less), 0.1% by mass or more and 5% by mass or less, or 0.1% by mass or more and 3% by mass or less (or 1.2% by mass or less).

[0061] (Barium Sulfate) The content of barium sulfate in the negative electrode material is, for example, 0.05% by mass or more, and may be 0.10% by mass or more. The content of barium sulfate in the negative electrode material is, for example, 3% by mass or less, and may be 2% by mass or less.

[0062] The content of barium sulfate in the negative electrode material may be from 0.05 to 3% by mass, from 0.05 to 2% by mass, from 0.10 to 3% by mass, or from 0.10 to 2% by mass.

[0063] (Measurement of specific conductance) The specific conductance of each of the positive and negative electrode materials is measured by the following procedure. First, a fully charged lead-acid battery after chemical formation is disassembled to remove the plates (positive and negative plates). Next, the removed plates are washed with water to remove the sulfuric acid from the plates. The plates are washed with water until a pH test paper is pressed against the washed surface of the plate and the color of the test paper does not change. The washed plates are dried at 60±5°C until completely dry, and then the conductance G1 of the plates is measured with a tester at 25±2°C. The negative plates are dried using a vacuum dryer. The tester used is a HIOKI Battery Hi-Tester BT3562A (using a pin-type probe). When using the tester, the positive probe is placed vertically at the center of the upper frame (top of the current collector) and the negative probe is placed vertically at the center of the lower frame (bottom of the current collector) to measure each conductance. The conductance of each plate is measured five times, and the average value is calculated. The average value of the conductance of all plates taken out by disassembling the lead-acid battery is adopted as the conductance G1 of the plate. Next, the plate height h and the cross-sectional area S of the plate are measured using the plate dried in the above procedure. The shortest distance between the top and bottom ends of the plate is taken as the plate height h, and is measured using a straight ruler. Next, the area of ​​the cross section perpendicular to the height direction of the plate is measured as the cross-sectional area S of the plate. Specifically, first, the length a of the long side (width of the plate) and the length b of the short side (thickness of the plate) are measured with a vernier caliper for four cross sections with distances from the bottom end of the plate of (1 / 5)h, (2 / 5)h, (3 / 5)h, and (4 / 5)h. At this time, when measuring b, the length b of each pair of opposing short sides is measured, and the average value is adopted. Then, the cross-sectional areas of the four locations, which are (1 / 5)h, (2 / 5)h, (3 / 5)h, and (4 / 5)h, are calculated from the respective values ​​of a×b, and the average of the cross-sectional areas of the four locations is adopted as the cross-sectional area S of the electrode plate. Next, the electrode material is removed from the electrode plate, and the current collector from which the electrode material has been removed is immersed in an alkaline mannitol solution for a predetermined period of time, and then washed with water to leave only the current collector, and the conductance G2 of the current collector is measured with a tester at 25±2°C. A HIOKI Battery HiTester BT3562A (using a pin-type probe) is used as the tester.The positive and negative probes are placed perpendicularly to the above-mentioned parts. The conductance of each current collector is measured five times, and the average value is calculated. The average conductance of all the current collectors taken out by disassembling the lead-acid battery is used as the conductance G2 of the current collector.

[0064] Then, the conductance G of the electrode material is calculated by formula (2), and the specific conductance is calculated by formula (1). Note that the conductance G is the reciprocal of the resistance. By adopting the specific conductance calculated by formula (1), the electrical conductivity of the electrode material can be evaluated without depending on the amount of electrode material. For example, by increasing the temperature of the flash drying furnace after filling the paste, cracks are easily generated in the electrode material, and the specific conductance can be reduced. Flash drying is performed before the paste maturation process, and is a process in which the electrode plate after filling the paste is passed directly through a tunnel-type furnace to dry it, and has the characteristic that only the surface of the electrode plate can be dried in a short time. As another method, for example, by increasing the temperature of the electrolyte during formation, the number of pores in the electrode material increases, and the specific conductance can be reduced. In addition, for example, by reducing the amount of charged electricity during formation, the amount of lead sulfate, which is a non-conductor, increases in the electrode material, and the specific conductance can be reduced. By these methods, the specific conductance can be controlled. Equation (1): Specific conductance = G × h / S (G: conductance of electrode material, h: height of electrode plate, S: cross-sectional area of ​​electrode plate) Equation (2): G = G1 - G2 (G1: Conductance of the electrode plate, G2: Conductance of the current collector)

[0065] The specific conductance of the positive electrode material may be controlled by changing the flash drying conditions according to other conditions that affect the specific conductance of the positive electrode material (for example, the electrolyte temperature during the chemical formation of the positive electrode material). The specific conductance of the negative electrode material may be controlled by changing the flash drying conditions according to other conditions that affect the specific conductance of the negative electrode material (for example, the electrolyte temperature during the chemical formation of the negative electrode material). The flash drying of the positive electrode material and the negative electrode material may be performed by heat treating the electrode plate after filling with the paste for a period of time ranging from 10 to 50 seconds in a drying oven having a temperature range of 300°C to 450°C, for example, or may be performed for a period of time ranging from 40 to 90 seconds in a drying oven having a temperature range of 200°C to 400°C. When flash drying is performed under the above conditions, the specific conductance of the positive electrode material and the specific conductance of the negative electrode material are easily controlled in a low range.

[0066] (Measurement of the ratio SP1 / SP0) The area SP0 of the lattice part of the positive electrode current collector obtained by the above procedure is obtained. The area SP0 of the lattice part is the area of ​​the smallest rectangle surrounding the outer edge of the lattice part. For example, the area SP0 can be obtained from the distance between the lower end of the upper frame part and the upper end of the lower frame part, and the length in the width direction of the lattice part. Next, the total area SP1 of the area surrounded by the lattice bars of the lattice part is obtained. The area SP1 is the total area of ​​the area surrounded by the lattice bars when viewed from above. The area SP1 is obtained by measuring each area from the height and width of each square surrounded by the lattice bars, and the width of the node part, and adding up each area. At this time, the area surrounded by the upper frame part and the lower frame part of the positive electrode current collector and the lattice bars is also defined as SP1. The ratio SP1 / SP0 is calculated from the obtained SP0 and SP1. The ratio SP1 / SP0 can be controlled by changing the cutting position of the positive electrode current collector or the node pitch (the distance between the nodes of the lattice bars in the width direction of the current collector).

[0067] The distance between the lower end of the upper frame part of the positive electrode current collector and the upper end of the lower frame part is, for example, 300 mm or less, and may be, for example, 200 mm or less, 150 mm or less, 120 mm or less, or 80 mm or less. The length in the width direction of the lattice part of the positive electrode current collector is, for example, 250 mm or less, and may be, for example, 200 mm or less, 150 mm or less, 120 mm or less, or 80 mm or less. By setting the size of the positive electrode current collector within the above range, it is possible to reduce the risk that the squares surrounded by the lattice bars become too large, making it difficult to uniformize the charge and discharge reaction of the positive electrode material throughout the entire electrode plate, which is preferable.

[0068] (Measurement of the ratio SN1 / SN0) The areas SN1 and SN0 of the negative electrode current collector can be determined in the same manner as the areas SP0 and SP1 of the positive electrode current collector. The ratio SN1 / SN0 can be controlled by changing the cutting position of the negative electrode current collector or the node pitch (the distance between the nodes of the lattice bars in the width direction of the current collector).

[0069] The distance between the lower end of the upper frame part of the negative electrode current collector and the upper end of the lower frame part is, for example, 300 mm or less, and may be 200 mm or less, 150 mm or less, 120 mm or less, or 80 mm or less. The length in the width direction of the lattice part of the negative electrode current collector is, for example, 250 mm or less, and may be 200 mm or less, 150 mm or less, 120 mm or less, or 80 mm or less. By setting the size of the negative electrode current collector within the above range, it is possible to reduce the risk that the squares surrounded by the lattice bars become too large, making it difficult to uniformize the charge and discharge reaction of the negative electrode material throughout the entire electrode plate, which is preferable.

[0070] (BET specific surface area measurement) The BET specific surface area of ​​the positive electrode material and the negative electrode material is determined by the following method. A fully charged lead-acid battery after formation is disassembled to remove the positive and negative plates. Next, the positive and negative plates are washed with water to remove the sulfuric acid from each plate. Washing is continued until the surface of the plate becomes neutral. Whether the surface of the plate is neutral can be confirmed by pressing a pH test paper against the surface of the plate. Each washed plate is dried at 60±5°C until it is completely dry. In addition, a vacuum dryer is used to dry the negative plate. Next, the positive electrode material is separated from the positive plate to obtain unground sample A, and the negative electrode material is separated from the negative plate to obtain sample B. Each sample is pretreated by heating at 150°C for 1 hour in a nitrogen flow. The BET specific surface area of ​​each pretreated sample is determined by mass measurement, measurement by gas adsorption method, and calculation using the BET formula. Specifically, the BET specific surface area is determined by measurements using the following equipment and conditions and the following calculations. Methods for increasing the BET specific surface area include reducing the particle size of the lead powder, lowering the temperature of the electrolyte during formation, and lowering the specific gravity of the electrolyte during formation. Measurement equipment: Micromeritics TriStar3000 Adsorption gas: Nitrogen gas with a purity of 99.99% or higher Adsorption temperature: liquid nitrogen boiling point (77K) Calculation method for BET specific surface area: Complies with 7.2 of JIS Z 8830:2013

[0071] The BET specific surface area of ​​the positive electrode material may be controlled by changing the electrolyte temperature during formation according to other conditions (such as the particle size of lead powder in the positive electrode material) that affect the BET specific surface area of ​​the positive electrode material. The BET specific surface area of ​​the negative electrode material may be controlled by changing the electrolyte temperature during formation according to other conditions (such as the particle size of lead powder in the negative electrode material) that affect the BET specific surface area of ​​the negative electrode material. The electrolyte temperature during formation of the positive electrode material and the negative electrode material may be in the range of 25°C to 80°C. By lowering the electrolyte temperature during formation within the above temperature range, the BET specific surface area of ​​the positive electrode material and the BET specific surface area of ​​the negative electrode material are easily controlled within a large range.

[0072] (Separator) A lead-acid battery usually includes a separator interposed between a negative electrode plate and a positive electrode plate. A microporous membrane or a nonwoven fabric can be used as the separator. A nonwoven fabric is a mat in which fibers are intertwined without being woven, and is mainly composed of fibers. For example, 60% or more of the nonwoven fabric is made of fibers. The nonwoven fabric may contain components other than fibers, such as acid-resistant inorganic powder (e.g., silica powder, glass powder, diatomaceous earth), and polymers as binders.

[0073] As the fibers, glass fibers, organic fibers, etc. can be used. As the organic fibers, fiber materials insoluble in the electrolyte are used. As the organic fibers, for example, polymer fibers (polyolefin fibers, acrylic fibers, polyester fibers (polyethylene terephthalate fibers, etc.)), pulp fibers, etc. can be used.

[0074] The nonwoven fabric preferably contains at least glass fiber. A nonwoven fabric containing glass fiber is also called an AGM (Absorbed Glass Mat) separator. The nonwoven fabric may contain glass fiber and organic fiber. The proportion of glass fiber in the total fibers constituting the nonwoven fabric is preferably 60 mass % or more.

[0075] The separator may be composed of only nonwoven fabric. If necessary, the separator may be a laminate of nonwoven fabric and a microporous membrane, a laminate of nonwoven fabric and a different or similar material, or a laminate of nonwoven fabric and a different or similar material with projections and recesses interlocked.

[0076] The microporous membrane is a porous sheet mainly composed of components other than fiber components, and can be obtained, for example, by extruding a composition containing a pore-forming agent into a sheet, and then removing the pore-forming agent to form pores. The microporous membrane is preferably made of an acid-resistant material, and is preferably microporous mainly composed of a polymer component. The polymer component is preferably polyolefin (polyethylene, polypropylene, etc.). The pore-forming agent can be at least one selected from the group consisting of polymer powder and oil.

[0077] The thickness of the separator interposed between the negative and positive electrode plates may be selected according to the distance between the electrodes, and the number of separators may be selected according to the number of gaps between the electrodes.

[0078] (electrolyte) The electrolyte is an aqueous solution containing sulfuric acid, which may be gelled as necessary.

[0079] The electrolytic solution may contain cations (e.g., metal cations) and / or anions (e.g., anions other than sulfate anions (e.g., phosphate ions)) as necessary. Examples of metal cations include at least one selected from the group consisting of Na ions, Li ions, Mg ions, and Al ions.

[0080] The specific gravity of the electrolyte in a fully charged lead-acid battery at 20° C. is, for example, 1.20 or more, and may be 1.25 or more. The specific gravity of the electrolyte at 20° C. is 1.35 or less, and preferably 1.32 or less.

[0081] (others) The lead-acid battery can be obtained by a manufacturing method including a step of housing a plate group and an electrolyte in a cell chamber of a battery case. Each cell of the lead-acid battery includes a plate group and an electrolyte housed in each cell chamber. The plate group is assembled by stacking a positive electrode plate, a negative electrode plate, and a separator such that the separator is interposed between the positive electrode plate and the negative electrode plate prior to housing in the cell chamber. The positive electrode plate, the negative electrode plate, the electrolyte, and the separator are each prepared prior to assembling the plate group. The manufacturing method of the lead-acid battery may include a step of chemically forming at least one of the positive electrode plate and the negative electrode plate, as necessary, after the step of housing the plate group and the electrolyte in the cell chamber.

[0082] The number of electrode plates in the electrode plate group included in one cell may be one, or two or more.

[0083] FIG. 1 is a cross-sectional view showing a schematic structure of an example of a lead-acid battery according to this embodiment. The lead-acid battery 1 includes an electrode plate group 11, an electrolyte (not shown), and a battery case 12 that accommodates them. The inside of the battery case 12 is divided into a plurality of cell chambers 14 by partition walls 13. Each cell chamber 14 accommodates one electrode plate group 11. The opening of the battery case 12 is closed by a lid 15 having a negative electrode terminal 16 and a positive electrode terminal 17. The lid 15 is provided with a vent plug 18 for each cell chamber. When rehydrating, the vent plug 18 is removed and rehydration liquid is replenished. The vent plug 18 may have a function of discharging gas generated in the cell chamber 14 to the outside of the battery.

[0084] Each electrode plate group 11 is formed by stacking a plurality of negative electrode plates 2 and positive electrode plates 3 with separators 4 interposed therebetween. FIG. 1 shows an example in which the negative electrode plates 2 are housed in a pouch-shaped separator 4. In a cell chamber 14 located at one end of the battery case 12, a negative electrode shelf portion 6 that connects a plurality of negative electrode plates 2 in parallel is connected to a through-connector 8, and a positive electrode shelf portion 5 that connects a plurality of positive electrode plates 3 in parallel is connected to a positive electrode column 7. The positive electrode column 7 is connected to a positive electrode terminal 17 outside the lid 15. In a cell chamber 14 located at the other end of the battery case 12, a negative electrode column 9 is connected to the negative electrode shelf portion 6, and a through-connector 8 is connected to the positive electrode shelf portion 5. The negative electrode column 9 is connected to a negative electrode terminal 16 outside the lid 15. Each through-connector 8 passes through a through hole provided in the partition wall 13 to connect the electrode plate groups 11 of adjacent cell chambers 14 in series. At least one of the negative electrode plate 2 and the positive electrode plate 3 is an electrode plate of the present invention.

[0085] Although FIG. 1 shows an example of a flooded battery (vented battery), the lead acid battery may be a valve regulated battery (VRLA type). In a flooded battery, the electrolyte is more likely to move than in a valve regulated battery, so that the discharge reaction is more likely to be uniform. Therefore, by using at least one of the positive and negative electrode plates according to this embodiment, a thin film of lead sulfate is more likely to be formed, and a high sulfation suppression effect can be obtained. For the above reasons, at least one of the positive and negative electrode plates according to this embodiment is preferably used in a flooded battery.

[0086] The test battery used in the performance evaluation in this specification has a rated voltage of 2 V / cell and a rated 5-hour rate capacity of 25 Ah.

[0087] FIG. 2A shows a top view of the current collectors (positive electrode current collector, negative electrode current collector) according to this embodiment. The current collector 20 shown in FIG. 2A includes ears 21, an upper frame portion 22, a lower frame portion 23, and a lattice portion 24. The lattice portion 24 is formed by lattice bars 25. Nodes 26 are formed at the portions where the lattice bars 25 intersect. The area of ​​the lattice portion 24 (areas SP0, SN0) is the area of ​​the smallest rectangular region 24s that surrounds the outer edge of the lattice portion 24. Note that in FIG. 2A, the region 24s is indicated by a dotted line.

[0088] Area 25s surrounded by lattice bars 25 of lattice portion 24 is shown by hatching in Fig. 2B (top view of current collector). The sum of areas 25s surrounded by closed ring-shaped structures formed by lattice bars 25 is area SP1 (or area SN1). As described above, in calculating areas SP1 and SN1, upper frame portion 22 and lower frame portion 23 are also considered to be part of the lattice bars. As shown in Fig. 2B, areas that do not form a closed ring-shaped structure and parts of lattice bars 25 (including parts of nodes) are not included in area SP1 (or area SN1).

[0089] <Calculation method for lead sulfate amount> First, a fully charged lead-acid battery is used, and the following charge / discharge cycle is repeated 600 times in a water tank at 10°C ± 2°C. The cell is then disassembled, the plates are removed, washed with water, and dried. The negative plates are dried in a vacuum dryer. After washing and drying, the plate is divided into three equal parts vertically, and about 20 g of electrode material is taken from the center of the bottom part to use as an electrode material sample. The sample is crushed and burned at high temperature. The sulfur contained in the electrode material is gasified to produce sulfur dioxide. The concentration of sulfur dioxide gas is measured using an infrared detector to determine the amount of sulfur contained in the sample. The ratio of the amount of lead atoms forming lead sulfate to the total amount of lead atoms contained in the sample is determined. The amount of lead sulfate contained in the electrode material is calculated from this ratio. <Charge / discharge cycle conditions> Step 1: Discharge at 45A for 59 seconds Step 2: Discharge at 300A for 1 second Step 3: Constant voltage charge for 60 seconds at 2.3V / cell and maximum current of 100A

[0090] <Cycle life test> Using a fully charged lead-acid battery, the above-mentioned steps 1 to 3 are repeated until the end of the battery life is determined in a water tank at 10° C.±2° C. At this time, the discharge end voltage in step 2 is measured, and the end of the battery life is determined when the discharge end voltage at the end of step 2 is less than 1.2 V / cell.

[0091] A positive electrode plate for a lead-acid battery, a negative electrode plate for a lead-acid battery, and a lead-acid battery according to one aspect of the present invention will be collectively described below.

[0092] (1) A positive electrode plate for a lead-acid battery, A positive electrode current collector and a positive electrode material held by the positive electrode current collector, The positive electrode material has a specific conductance of 1.8 S / mm or less.

[0093] (2) the positive electrode current collector includes a lattice portion, The positive electrode plate for a lead-acid battery according to the above (1), wherein the ratio SP1 / SP0 of the total area SP1 of the area surrounded by the lattice bars of the lattice portion to the area SP0 of the lattice portion of the positive electrode current collector is 0.68 or more.

[0094] (3) The BET specific surface area of ​​the positive electrode material is 5.8 m 2 / g or more.

[0095] (4) A negative electrode plate for a lead-acid battery, A negative electrode current collector and a negative electrode material held by the negative electrode current collector, The negative electrode material has a specific conductance of 120 S / mm or less.

[0096] (5) The negative electrode current collector includes a lattice portion, The negative electrode plate for a lead-acid battery according to the above (4), wherein a ratio SN1 / SN0 of a total area SN1 of the area surrounded by the lattice bars of the lattice portion to an area SN0 of the lattice portion of the negative electrode current collector is 0.65 or more.

[0097] (6) The BET specific surface area of ​​the negative electrode material is 0.75 m 2 / g or more.

[0098] (7) A lead-acid battery comprising at least one of the positive electrode plate for a lead-acid battery according to any one of (1) to (3) above and the negative electrode plate for a lead-acid battery according to any one of (4) to (6) above.

[0099] [Example] The present invention will be specifically described below based on examples and comparative examples, but the present invention is not limited to the following examples.

[0100] ≪Lead acid batteries A1~A5, B1~B5, C1~15, D1~D15, E1~E12, F1~F12≫ (1) Preparation of the positive electrode current collector A positive current collector made of an expanded lattice made of a Pb-Ca-Sn alloy is prepared as shown in Figure 2A. The distance between the bottom end of the upper frame part of the positive current collector and the top end of the lower frame part is 115 mm, and the length of the lattice part in the width direction is 100 mm. The ratio SP1 / SP0 was controlled by changing the cutting position of the positive current collector and the distance between the nodes, and the positive current collector was prepared so as to have the values ​​shown in the table below.

[0101] (2) Preparation of negative electrode current collector A negative electrode current collector made of an expanded lattice made of a Pb-Ca-Sn alloy is prepared as shown in Figure 2A. The distance between the bottom end of the upper frame part of the negative electrode current collector and the top end of the lower frame part is 115 mm, and the length of the lattice part in the width direction is 100 mm. The ratio SN1 / SN0 was controlled by changing the cutting position of the negative electrode current collector and the distance between the nodes, and the negative electrode current collector was prepared so as to have the values ​​shown in the table below.

[0102] (3) Preparation of the positive electrode plate The raw lead powder and sulfuric acid solution are mixed to obtain a positive electrode paste. The positive electrode paste is filled into an expanded grid made of Pb-Ca-Sn alloy, flash-dried, and then aged and dried to obtain an unformed positive electrode plate. The temperature of the flash-drying furnace was controlled so that the specific conductance of the positive electrode material would be the value shown in the table below. In addition, the BET specific surface area of ​​the positive electrode material was changed by controlling the temperature of the electrolyte during formation.

[0103] (4) Preparation of negative electrode plate The raw material lead powder, lignin as an organic shrinkage inhibitor, barium sulfate, and carbon black are mixed with an appropriate amount of sulfuric acid aqueous solution to obtain a negative electrode paste. The negative electrode paste is filled into an expanded grid made of Pb-Ca-Sn alloy, flash-dried, and then aged and dried to obtain an unformed negative electrode plate. At this time, the temperature of the flash-drying furnace was controlled so that the specific conductance of the negative electrode material would be the value shown in the table below. In addition, the BET specific surface area of ​​the negative electrode material was changed by controlling the electrolyte temperature during formation.

[0104] (5) Making a lead-acid battery The test battery had a rated voltage of 2V / cell and a rated 5-hour capacity of 25Ah. The plate group of the test battery was composed of 5 positive plates and 5 negative plates. The positive and negative plates were alternately stacked with a separator between them to form a plate group. The plate group was placed in an ABS battery case and sealed with a lid. A polyethylene microporous film was used as the separator. After injecting the electrolyte, the plate group was chemically treated in the battery case to prepare a lead-acid battery. The chemical treatment brought the lead-acid battery to a fully charged state. The specific gravity of the electrolyte in the fully charged lead-acid battery at 20°C was 1.33. The positive and negative plates constituting the test battery were configured so that all the positive and negative plates had the "specific conductance", "ratio SP1 / SP0", "SN1 / SN0" and "BET specific surface area" shown in the table below. The negative electrodes of the batteries shown in Tables 1, 3, and 5 were the same as those used in Battery B1. The positive electrodes of the batteries shown in Tables 2, 4, and 6 were the same as those used in Battery A1.

[0105] (6) Evaluation (a) Amount of lead sulfate in the lower part of the positive electrode and the lower part of the negative electrode The amount of lead sulfate in the lower part of the positive electrode and the amount of lead sulfate in the lower part of the negative electrode were calculated by the method described above.

[0106] (b) Cycle life performance A cycle life test was carried out by the method described above to evaluate the cycle life performance.

[0107] The results are shown in Tables 1 to 6. For the "amount of lead sulfate in the lower part of the positive electrode," "amount of lead sulfate in the lower part of the negative electrode," and "cycle life performance," in Tables 1, 3, and 5, the values ​​are expressed as relative values ​​when the value for Battery A1 is set to 100, and in Tables 2, 4, and 6, the values ​​are expressed as relative values ​​when the value for Battery B1 is set to 100.

[0108] [Table 1]

[0109] Among the batteries shown in Table 1, batteries A1 and A2 are comparative examples, and batteries A3 to A5 are examples. The BET specific surface area of ​​the positive electrode material of the batteries shown in Table 1 is 4.6 m 2 / g. From Table 1, it can be seen that the amount of lead sulfate in the lower part of the positive electrode tends to decrease by decreasing the specific conductance of the positive electrode material, and the amount of lead sulfate in the lower part of the positive electrode is greatly decreased when the specific conductance of the positive electrode material is 1.8 S / mm or less. The reason for this is thought to be that the discharge reaction is difficult to reach the inside of the positive electrode material, the discharge reaction that generates lead sulfate is biased toward the surface of the electrode material, and a thin layer of lead sulfate is easily formed near the surface of the electrode material. It is also presumed that lead sulfate is difficult to form inside the positive electrode material, and the coarsening of lead sulfate remaining inside the positive electrode material is suppressed, thereby suppressing the lead sulfate from remaining inside the positive electrode material. As a result, it is thought that sulfation in the positive plate is suppressed and the cycle life performance is improved. From the above, it is preferable that the specific conductance of the positive electrode material is 1.8 S / mm or less.

[0110] [Table 2]

[0111] Among the batteries shown in Table 2, batteries B1 and B2 are comparative examples, and batteries B3 to B5 are examples. The BET specific surface area of ​​the negative electrode material of the batteries shown in Table 2 is 0.65 m 2 / g. Table 2 shows that the amount of lead sulfate in the lower part of the negative electrode tends to decrease by decreasing the specific conductance of the negative electrode material, and the amount of lead sulfate in the lower part of the negative electrode is greatly reduced when the specific conductance of the negative electrode material is 120 S / mm or less. The reason for this is presumed to be that, similar to the mechanism presumed for the positive electrode material described above, a thin layer of lead sulfate is easily formed near the surface of the electrode material, and lead sulfate is also suppressed from remaining inside the negative electrode material. For these reasons, it is preferable that the specific conductance of the negative electrode material is 120 S / mm or less.

[0112] [Table 3]

[0113] Among the batteries shown in Table 3, batteries A3 to A5, batteries C3 to C5, batteries C8 to C10, and batteries C13 to C15 are examples, and the rest are comparative examples. From Table 3, it was found that the amount of lead sulfate in the lower part of the positive electrode was reduced by increasing the ratio SP1 / SP0 of the positive electrode collector, and the amount of lead sulfate in the lower part of the positive electrode was further reduced by reducing the specific conductance of the positive electrode material. Specifically, by setting the ratio SP1 / SP0 of the positive electrode collector to 0.68 or more and the specific conductance of the positive electrode material to 1.8 S / mm or less, the amount of lead sulfate in the lower part of the positive electrode was synergistically reduced, and the cycle life performance was synergistically improved. The reason for this is thought to be that the area not surrounded by the lattice bars of the positive electrode collector at the end of the collector, where current does not easily flow, becomes smaller, making it easier for the charge / discharge reaction of the positive electrode material to be uniform throughout the entire plate. As a result, it is presumed that the charge / discharge reaction is less likely to concentrate in a specific area on the plate, making it easier to form a thin layer of lead sulfate near the surface of the positive electrode material. For these reasons, it is preferable that the ratio SP1 / SP0 of the positive electrode current collector is 0.68 or more and the specific conductance of the positive electrode material is 1.8 S / mm or less.

[0114] [Table 4]

[0115] Among the batteries shown in Table 4, batteries B3 to B5, batteries D3 to D5, batteries D8 to D10, and batteries D13 to D15 are examples, and the rest are comparative examples. From Table 4, it was found that the amount of lead sulfate in the lower part of the negative electrode tends to decrease by increasing the ratio SN1 / SN0 of the negative electrode collector, and in addition, the amount of lead sulfate in the lower part of the negative electrode tends to decrease further by decreasing the specific conductance of the negative electrode material. Specifically, by setting the ratio SN1 / SN0 of the negative electrode collector to 0.65 or more and the specific conductance of the negative electrode material to 120 S / mm or less, the amount of lead sulfate in the lower part of the negative electrode was synergistically decreased, and the cycle life performance was synergistically improved. The reason for this is that, similar to the mechanism assumed for the positive electrode collector described above, the area not surrounded by the lattice bars of the negative electrode collector at the end of the collector where current does not easily flow becomes smaller, making it difficult for the charge / discharge reaction to concentrate in a specific area on the electrode plate, and making it easier to form a thin layer of lead sulfate near the surface of the negative electrode material. For these reasons, it is preferable that the ratio SN1 / SN0 of the negative electrode current collector is 0.65 or more and the specific conductance of the negative electrode material is 120 S / mm or less.

[0116] [Table 5]

[0117] Among the batteries shown in Table 5, the batteries in which the specific conductance of the positive electrode material is 1.8 S / mm or less are examples, and the rest are comparative examples. From Table 5, it can be seen that the amount of lead sulfate in the lower part of the positive electrode tends to decrease by increasing the BET specific surface area of ​​the positive electrode material, and furthermore, it can be seen that the amount of lead sulfate in the lower part of the positive electrode tends to decrease by decreasing the specific conductance of the positive electrode material. Specifically, when the BET specific surface area of ​​the positive electrode material is increased to 5.8 m 2By setting the BET specific surface area of ​​the positive electrode material at 5.8 m / g or more and the specific conductance of the positive electrode material at 1.8 S / mm or less, the amount of lead sulfate in the lower part of the positive electrode was reduced synergistically, and the cycle life performance was improved synergistically. The reason for this is presumably that when the BET specific surface area is larger than a certain value, the charge / discharge reaction can take place over a wide surface of the positive electrode material, making it easier to form a thinner lead sulfate layer. For these reasons, it was found that the BET specific surface area of ​​the positive electrode material was set at 5.8 m 2 / g or more and the specific conductance of the positive electrode material is preferably 1.8 S / mm or less.

[0118] [Table 6]

[0119] Among the batteries shown in Table 6, the batteries in which the specific conductance of the negative electrode material is 120 S / mm or less are examples, and the rest are comparative examples. From Table 6, it can be seen that the amount of lead sulfate in the lower part of the negative electrode tends to decrease by increasing the BET specific surface area of ​​the negative electrode material, and furthermore, it can be seen that the amount of lead sulfate in the lower part of the negative electrode tends to decrease by decreasing the specific conductance of the negative electrode material. Specifically, when the BET specific surface area of ​​the negative electrode material is 0.75 m 2 By setting the specific conductance of the negative electrode material at 120 S / mm or more and the specific conductance of the negative electrode material at 120 S / mm or less, the amount of lead sulfate in the lower part of the negative electrode was synergistically reduced, and the cycle life performance was synergistically improved. The reason for this is presumed to be that, similar to the mechanism presumed for the positive electrode material described above, when the BET specific surface area is larger than a certain value, the charge / discharge reaction can take place on a wide surface of the negative electrode material, making it easier to form a thinner lead sulfate layer. For these reasons, it was found that the BET specific surface area of ​​the negative electrode material was set to 0.75 m 2 / g or more and the specific conductance of the negative electrode material is preferably 120 S / mm or less. [Industrial Applicability]

[0120] The present invention can be used in a positive electrode plate for a lead-acid battery, a negative electrode plate for a lead-acid battery, and a lead-acid battery. [Explanation of symbols]

[0121] 1:Lead acid battery 2: Negative plate 3: Positive plate 4: Separator 11: Plate group 12:Battery container 20: Current collector (positive electrode current collector, negative electrode current collector) 21: Ears 22: Upper frame part 23: Lower frame bone 24: Lattice part 24s: The area surrounding the outer edge of the lattice 25: Lattice 25s: Area surrounded by the lattice bars of the lattice-shaped part 26: Node

Claims

1. A positive electrode plate for a lead-acid battery, A positive electrode current collector and a positive electrode material held by the positive electrode current collector, The positive electrode material has a specific conductance of 1.8 S / mm or less.

2. The positive electrode current collector includes a lattice portion, 2. The lead-acid battery positive plate according to claim 1, wherein the ratio SP1 / SP0 of the total area SP1 of the area surrounded by the lattice bars of the lattice portion to the area SP0 of the lattice portion of the positive electrode collector is 0.68 or more.

3. The BET specific surface area of ​​the positive electrode material is 5.8 m 2 The positive electrode plate for a lead-acid battery according to claim 1, wherein the Mo content is 1 / g or more.

4. A negative electrode plate for a lead-acid battery, A negative electrode current collector and a negative electrode material held by the negative electrode current collector, The negative electrode material has a specific conductance of 120 S / mm or less.

5. The negative electrode current collector includes a lattice portion, 5. The negative electrode plate for a lead-acid battery according to claim 4, wherein the ratio SN1 / SN0 of the total area SN1 of the area surrounded by the lattice bars of the lattice portion to the area SN0 of the lattice portion of the negative electrode collector is 0.65 or more.

6. The BET specific surface area of ​​the negative electrode material is 0.75 m 2 The negative electrode plate for a lead acid battery according to claim 4, wherein the molecular weight of the negative electrode plate is 1.0 / g or more.

7. A lead-acid battery comprising at least one of the positive electrode plate for a lead-acid battery according to any one of claims 1 to 3 and the negative electrode plate for a lead-acid battery according to any one of claims 4 to 6.

Citation Information

Patent Citations

  • Oxide conductive ceramics flake and its manufacture

    JP1994187820A

  • Electrode plate for lead-acid battery

    JP1995320743A

  • Expanded mesh sheet and manufacture and device thereof

    JP1998223232A